Ethno-Musicology - Kunst, Jaap. author. aut Link
158 p. 46 illus.
Keywords: This booklet hardly needs a preface; the contents, I think, speak for themselves. It contains a short and carefully brought up to date resume of all that I, as a private University Lecturer in Amsterdam, have tried to teach my pupils. It is intended as a general introduction to ethno-musicology, before going on to the study of the forms of separate music-cultures. I sincerely hope that those, who wish to teach themselves and to qualify in this branch of knowledge, will find a satisfactory basis for self tuition in the matter here brought together. Regarding the possibility of a new edition, any critical remarks or infor mation as to possible desiderata would be very gratefully received. J.K. PREFACE TO THE SECOND EDITION My request for critical remarks and desiderata has not been ignored. My sincere thanks to all who took the trouble to let me know what they missed in my booklet. Through their collaboration the contents have undergone a considerable improvement and enlargement as compared to the original edition issued in 1950 by the Royal Tropical Institute, Amsterdam, under the title 'Musicologica'. I have taken care to add many particulars from non-European sources, with the result that now the book is no longer so Europe-centric as it was.